Safe Medication Reconciliation: An Intervention to Improve Residents' Medication Reconciliation Skills - Arundel, Cherinne (J Grad Med Educ, 2015)
BACKGROUND: Medication errors during hospitalization are a major patient safety concern. Medication reconciliation is an effective tool to reduce medication errors, yet internal medicine residents rarely receive formal education on the process. OBJECTIVE: We assessed if an educational intervention on quality improvement principles and effective medication reconciliation for internal medicine residents will lead to fewer medication discrepancies and more accurate discharge medication lists. METHODS: From July 2012 to May 2013, internal medicine residents from 3 academic institutions who were rotating at the Washington DC VA Medical Center received twice-monthly interactive educational sessions on medication reconciliation, using both institutional summary metrics and data from their own discharges. Sessions were led by a faculty member or chief resident. Accuracy of discharge instructions for residents in the intervention group was compared to the accuracy of discharge data from June 2012 for a group of residents who did not receive the intervention. We used χ(2) analysis to assess for differences. RESULTS: The number of duplicate medications (23% versus 12%, P = .01); extraneous medications (14% versus 6%, P = .014); medications sorted by disease or indication (25% versus 77%, P < .001); and the number of discrepancies in discharge summaries (34% versus 11%, P < .001) statistically improved. No difference in the number of omissions was found between the 2 groups (17% versus 15%, P = .62). CONCLUSIONS: An educational intervention targeting internal medicine residents can be implemented with reasonable staff and time costs, and is effective in reducing the number of medication discrepancies at discharge.